Effect of calcium sprays on fruit quality and shelf-life of apple (Malus × domestica) - Chandel, J S; Sharma, Sanjeev; Verma, Pramod (The Indian Journal of Agricultural Sciences, 2019)
The present investigation was carried out during 2011- 2012 in an apple orchard situated 1935 m amsl in Shimla, district in Himachal Pradesh in order to assess the effect of foliar nutrition of calcium on growth, yield, fruit quality and shelf-life of apple. Two commercial grade calcium formulation, viz. CaCl2 at 0.4, 0.5 and 0.6% and Ca(NO3)2 at 0.2, 0.4 and 0.6 % were sprayed once (75 days after full bloom), thrice (45, 60 and 75 days after full bloom) and five times (15, 30, 45, 60 and 75 days after full bloom). The experiment was laid out in randomized block design with 19 treatments (replicated thrice). Two years pooled data revealed that five sprays of 0.6% Ca(NO3)2 significantly increased annual shoot growth and leaf area, but reduced the total yield, fruit size and weight. However, results of storage studies revealed that five sprays of 0.5 and 0.6% CaCl2 significantly reduced the physiological fruit weight loss, retain higher fruit firmness, TSS and sugar contents and improve the shelf-life of fruits in ambient storage conditions.